Extensive Exophytic Gum Swelling: A Case Study - Abdullah Saeidi; Mahir Mirah; Albraa Alolayan; Hattan Zaki; Shadia Elsayed (Reports)
Background and Clinical Significance: Large extensive intraoral dental swelling is uncommon in adults, and we report a rare case of large exophytic oral granulomatous tissue. A complete explanation of diagnostic steps and surgical treatments is addressed, as well as a thorough review of the literature, and a discussion of this interesting case is provided to underline the need for recognition of these vascular pyogenic proliferative lesions and discuss proper management based on the underlying cause. Case Presentation: A 21-year-old Afghan female patient who presented with an extensive intraoral pale red, friable lesion that bled easily. It was 15 × 15 mm in size related to the lower second molar, and interfered with occlusion and extended to cover the buccal and lingual surfaces of adjacent teeth. Conclusions: The presentation of this rare large reactive vascular proliferative condition of oral posterior gingiva, contribute to a better understanding and the growing body of evidence on the PG. The findings emphasize the importance of early intervention tailored to the patient’s age, lesion location, and underlying causes and patient education to prevent extensive dental tissue destruction.